Exploring particle system under unity 3D - Lim, Hui Xin (2017)
As the world is currently undergoing a digital revolution, also known as the Fourth Industrial Revolution, artificial intelligence (AI) is steadily transforming our lives, as well as disrupting the businesses of traditional industries. Incorporating AI into computer gaming is one of the most impactful results of current evolving technology. Artificial Intelligence (AI) refers to capability of computers to deduce and react to its surroundings in order to achieve a goal in the most efficient method. In recent years, the term is commonly affiliated to simulate humans’ cognition. Some of the AI approaches compromise of using metaheuristic algorithms. In this project, the movements of three metaphor-based metaheuristics algorithm will be studied in order to infuse AI into a game play. They are the Particle Swarm Optimisation (PSO), Ant Colony Optimisation (ACO) and Artificial Bee Colony System (ABC). Instead of comparing the efficiencies of the algorithms, this project will emphasise on the visual effect on a 3D plane. Finally, instead of the conventional Particle System in Unity 3D, the best algorithm will be picked to create particle effects in a simple game demo.